Pengaruh Bauran Pemasaran terhadap Loyalitas Nasabah pada Bank BRI Unit Ampek Nagari Cabang Bukittinggi - Nardiman Nardiman (Jurnal Riset dan Inovasi Manajemen, 2026)
This study aims to determine: 1) The effect of the product on customer loyalty, 2) Price influence on customer loyalty, 3) The influence of place / location on customer loyalty, 4) The influence of promotion on customer loyalty, 5) The influence of people / employees on customer loyalty, 6) Effect of physical facilities on customer loyalty, 7) Effect of process on customer loyalty Bank BRI Unit Ampek Nagari Cabang Bukittinggi. Type of research conducted is Expost-Facto, the number of study population as much as 834 people, Proportional sampling technique Simple Random Sampling. The sample of this research is customer Bank BRI Unit Ampek Nagari Cabang Bukittinggi numbered 114 people. Data were collected through questionnaires using Likert scale models that have been tested for validity and reliability. Data analysis technique used is Path Analysis (Path Analysis). The research results are: 1) There is significant influence between product to customer loyalty, 2) There is a significant influence between price and customer loyalty, 3) There is a significant influence between place / location on customer loyalty, 4) There is significant influence between promotion to customer loyalty, 5) There is significant influence between person / employee to customer loyalty Training, 6) There is significant influence between physical facility to customer loyalty, 7) There is a significant influence between the process on customer loyalty Bank BRI Unit Ampek Nagari Cabang Bukittinggi. Viewed from direct or indirect influence of product, price, place / location, promotion, person / employee, physical facility and process to customer's loyalty Bank BRI Unit Ampek Nagari Cabang Bukittinggi is 84.54%, it is obtained that the promotion has the greatest influence of 21.01%. This shows that the understanding of promotion directly has a big role to the emergence of customer loyalty Bank BRI Unit Ampek Nagari Cabang Bukittinggi.